Geographical Ideologies and Nature: The Re-Making of Forests and the Crisis of Capital - Luis Fernando De Matheus; Andrei Cornetta (Íconos)
This paper examines theoretical issues surrounding how conservation efforts are reproduced within contemporary capitalism drawing on two cases: Brazil’s eastern Amazon and the forested regions of southern Chile. Drawing on a critical approach to analyze the data from the respective cases, we analyze the ways in which conservation efforts have been territorialized and loaded with symbolism and diversity, which express different ideological geographies. We argue that in the contemporary crisis of capitalism (which has been misunderstood by many observers as an environmental crisis), an array of new commodities have emerged. These processes of commodification have been marked by the commodification of “environmental services” and the creation of more private nature reserves creating value in new ways marked by scarcity and unique natural attractions.